2019
DOI: 10.24093/awej/vol10no3.15
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions and Beliefs of Saudi Preparatory Year Program Learners Towards Learning English: A Case Study

Abstract: Learning English in the Kingdom of Saudi Arabia (KSA) can be a challenging experience. Nevertheless, being proficient in English language guarantees better job opportunities in various fields and thus learners need to acquire an acceptable level of proficiency. Recognizing its significant role in the learners' academic and professional excellence, the English language has gained the status of a mandatory language in the Saudi higher education institutions. As students enter universities for higher studies, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Massri discussed the factors affecting EFL in KSA, both student-and teacher-related factors. Student-related factors include social pressure, family expectations, propositions, and their goals to move abroad for higher studies [23]. Another recent study investigated the reasons for indifference to learning EFL.…”
Section: Discussionmentioning
confidence: 99%
“…Massri discussed the factors affecting EFL in KSA, both student-and teacher-related factors. Student-related factors include social pressure, family expectations, propositions, and their goals to move abroad for higher studies [23]. Another recent study investigated the reasons for indifference to learning EFL.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is more interest in the English language, which is viewed as the main medium through which instruction in these fields is delivered (Alshahrani, 2016). As Massri (2019) points out, "the English language has gained the status of a mandatory language in the Saudi higher education institutions" (p. 220). Through programs like the preparatory year program, students also have the chance to learn and improve their English before joining higher education institutions.…”
Section: History and Significance Of Bilingual Education In Saudi Arabiamentioning
confidence: 99%
“…The viewpoints of El-Hawat (2009), Al-Hussein (2014); Abuklaish (2014); Khalid (2017) about the political decision to stop teaching the English language in all sectors, negatively impacted the educational sector in Libya. Massri (2019) revealed that technology integration in the classroom was actively and positively associated with the passion and motivation of the EFL students. Her findings indicated a connection between the teaching material, its usage, and the student's motivation.…”
Section: Section Two: What Are Efl Lecturers' Perceptions Regarding S...mentioning
confidence: 99%